VL Shimla Mirch 3: a new sweet pepper variety - Hedau, N K; Bhatt, J C; Hooda, K S; Tuti, M; Stanley, J; Lal, Shankar; Dhar, Shri; Agrawal, P K (Indian Horticulture, 2019)
VL Shimla Mirch 3 is a new variety released for Uttarakhand. It is a selection from introduced AVRDC line (IC584767). This variety is first of its kind, which is suitable for off-season cultivation, especially in rainy season in hills. Its plants are straight, vigorous having bright dark green, blocky medium, bell-shaped fruits, which turn red on ripening. Average green fruit yield is 200-300 q/ha under midhills of Uttarakhand and suitable for cultivation in both organic and inorganic conditions.